Efecto de enmiendas orgánicas (compost y biochar) en dos variedades de Col (brassica oleracea) col repollo y col milán, en Salcedo, Cotopaxi 2021. - Eguez Bautista, Paul Vinicio (2021)
This research was conducted in the sector of Mulliquindil Santa Ana, Canton Salcedo, Province of Cotopaxi. The objective was to evaluate the effect of two organic amendments on two varieties of cabbage (Brassica oleracea var. Sabauda). A complete randomized design with a factorial arrangement of 2 x 2 x 3 + 2 was applied, giving a total of 14 treatments and 42 experimental units. The organic amendments used were compost and biochar, and the cabbage varieties were cabbage and Milan. The indicators to be evaluated were mortality percentage, plant height, leaf length and width, and yield. In addition, soil and bromatological analyses were performed. From the data obtained, it was determined that treatment T9 (cabbage Milan + compost 11.25 kg) presented the best averages for each indicator evaluated; in plant height, it obtained 19.72 cm; in leaf length, it reached 16.54 cm; for leaf width, it obtained an average of 13.51 cm 30 days after transplanting. The dose that presented the best results was D3 (11.25 kg), with averages of 42.53 cm for plant height, 27.38 cm for leaf length, and 21.29 cm for leaf width. The bromatological analysis showed the following results for the percentage of protein with 3.36%, fiber 5.78%, fat 0.65%, and ash with 2.58% of the cabbage samples of the two varieties sent to the laboratory. Treatment T4 (cabbage + biochar 1.32 kg) obtained the best cost-benefit among the established treatments with a value of $3.68 per kilogram harvested. In conclusion, the use of organic amendments had a positive effect on the treatments concerning the control.